Composite coating coated graphite composite negative electrode material and preparation method and application thereof

By using composite coating technology on graphite negative electrode materials, using niobium pentoxide and titanium dioxide to form a multi-layer structure, the shortcomings of traditional graphite negative electrode materials in fast charging performance and cycle stability are solved, and higher rate performance and structural stability are achieved.

CN119695051APending Publication Date: 2025-03-25安徽得壹能源科技有限公司

Patent Information

Application Number
CN202411905295.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Traditional graphite negative electrode materials are difficult to meet the current technical requirements in terms of fast charging performance, high safety performance and energy density, and the long-term cycle stability of graphite materials directly coated with niobium pentoxide is poor.

Method used

The composite coating is used to coat the graphite negative electrode material, and the graphite is coated by niobium pentoxide and then coated with titanium dioxide to form a structure in which niobium pentoxide is an intermediate layer, titanium dioxide is an outer shell, and graphite is an inner shell.

Benefits of technology

It improves the rate performance and cycle stability of the material, reduces the interface impedance, enhances the stability of the structure, and improves the fast charging capability and long-term cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695051A_ABST
    Figure CN119695051A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery materials, and provides a composite coating coated graphite composite negative electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: (1) preparing a niobium pentoxide coated graphite precursor material; and (2) coating the niobium pentoxide coated graphite precursor material with a titanium dioxide coating by adopting a sol-gel method, and calcining to obtain the niobium pentoxide coated graphite composite material. According to the prepared composite coating coated graphite negative electrode material, the niobium pentoxide coating can reduce the interface impedance, and the titanium dioxide coating can ensure the stability of the structure. Therefore, the negative electrode not only has excellent rate capability, but also keeps excellent cycling stability, and the preparation method is simple and convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery materials and relates to a composite coating-coated graphite composite negative electrode material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Lithium-ion batteries are environmentally friendly electrochemical energy storage devices. With their high energy density, high operating voltage, fast charge and discharge capabilities, wide electrochemical window and environmentally friendly characteristics, they have been widely used in many fields such as consumer electronics, transportation power and new energy storage. As one of the four main materials of lithium-ion batteries, graphite anode is a key component for storing lithium ions in batteries and is known as the "energy warehouse" of lithium-ion batteries. Graphite anode is mainly composed of graphite material, conductive agent and binder, which work together to affect the performance of the anode. According to different application requirements, positive electrode material types and battery designs, researchers have developed a combination of various graphite materials (such as natural graphite, artificial graphite and its modified versions), conductive agents (such as carbon black, graphene, etc.) and binders (such as PVDF, SBR, etc.), aiming to achieve high specific capacity, long cycle life, excellent rate performance and good structural stability. Through these carefully designed formulas, graphite anode can support the efficient and stable operation of lithium-ion batteries with high energy density, fast charge and discharge and a wide temperature range.

[0004] With the increasing application of lithium-ion batteries in electric vehicles, portable electronic devices, energy storage systems and other fields, the market demand for high-power, high-energy-density lithium-ion batteries has increased dramatically. Traditional graphite negative electrode materials can no longer meet current technical requirements in terms of fast charging performance, high safety performance and energy density. Niobium pentoxide (Nb2O5) has become a research hotspot for negative electrode materials for lithium-ion batteries due to its unique fast lithium storage kinetics and high capacity characteristics. The interface resistance can be reduced and the fast charging capability of the battery can be improved by coating modified graphite with niobium pentoxide. For example, the niobium pentoxide-coated graphite composite negative electrode material proposed in patent CN114864916A improves the fast charging capability of graphite by coating graphite, and maintains a high level of capacity retention under 10C fast charging conditions.

[0005] However, the direct use of niobium pentoxide as anode material or anode graphite modified material has the problem of insufficient cycle stability, which is mainly due to its inherent insulation properties and structural degradation during the charge and discharge process. The porous niobium pentoxide structure is usually composed of interconnected nanoparticles with a large number of grain boundaries, which will cause serious structural degradation during long-term cycles. Although the modified graphite coated with niobium pentoxide can reduce the interface resistance, improve the cycle stability and fast charging capability, the cycle stability still needs to be further improved. Therefore, it is urgent to develop a new method for modifying the graphite anode, aiming to simultaneously improve the lithium ion deintercalation speed, cycle stability and rate performance of graphite. Summary of the invention

[0006] In order to solve the problem of poor long-term cycle stability of the above-mentioned niobium pentoxide directly coated graphite negative electrode material, the present invention provides a composite coating coated graphite negative electrode material and its preparation method and application, firstly, niobium pentoxide and graphite are used to form a niobium pentoxide coated graphite precursor material by a sol-gel method, and the precursor material is then used with a titanium source solution by a sol-gel method to prepare a composite coating coated graphite negative electrode material with titanium dioxide as the outer shell, niobium pentoxide as the middle layer, and graphite as the inner shell. The negative electrode has both excellent rate performance and excellent cycle stability, and the preparation method is simple.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a method for preparing a composite coating-coated graphite composite negative electrode material, comprising:

[0009] (1) preparing a niobium pentoxide-coated graphite precursor material;

[0010] (2) A titanium dioxide coating is coated on the niobium pentoxide-coated graphite precursor material by a sol-gel method, and the coating is calcined to obtain a titanium dioxide coating.

[0011] The present invention utilizes the excellent rate performance of niobium pentoxide and coats it on the surface of the graphite layer to reduce the interface impedance of the material and improve the rate performance of the material. Then, titanium dioxide is coated on the surface of niobium pentoxide to construct titanium niobium oxide with an octahedral lattice shear structure. These octahedral blocks are connected by shared edges and defined by lattice shear planes, thereby ensuring a high degree of structural stability and providing a large number of vacancies for lithium ion insertion to improve the stability of the structure during long-term cycles, thereby improving the cycle performance of the material.

[0012] Preferably, in the niobium pentoxide-coated graphite precursor material, the mass of niobium pentoxide accounts for 5%-15% of the total mass of niobium pentoxide and graphite.

[0013] Preferably, the specific preparation method of the niobium pentoxide-coated graphite precursor material includes: dissolving niobium pentoxide in anhydrous ethanol solution, adding water, stirring and preheating, adding graphite powder, heating and stirring until the liquid solvent is evaporated, drying to obtain solid powder, and calcining.

[0014] Preferably, in step (1), the mass volume ratio of niobium pentoxide to anhydrous ethanol solution is 1 g: 15-30 mL;

[0015] Preferably, in step (1), the volume ratio of anhydrous ethanol to water is 2-5:1;

[0016] Preferably, in step (1), the preheating temperature is 30-50° C. and the preheating time is 20-40 min.

[0017] Preferably, in step (1), the heating temperature is 65-85°C.

[0018] Preferably, in step (1), the calcination temperature is 600-800° C., and the calcination time is 2-4 hours.

[0019] Preferably, the specific preparation method of the titanium dioxide coating includes: dissolving the niobium pentoxide-coated graphite precursor material in an anhydrous ethanol solution, adding water, stirring and preheating, adding a titanium source solution dropwise, heating to react, and after the reaction is completed, separating the solid from the liquid, washing, and drying to obtain the titanium dioxide coating.

[0020] Preferably, in step (2), the preheating temperature is 30-50° C. and the preheating time is 20-40 min.

[0021] Preferably, in step (2), the heating temperature is 60-80° C. and the reaction time is 2-4 h.

[0022] Preferably, in step (2), the volume mass ratio of the titanium source solution to the precursor material is 0.5-2.5 mL: 1 g.

[0023] Preferably, in step (2), the mass volume ratio of the precursor material to the anhydrous ethanol solution is 1 g: 15-30 mL;

[0024] Preferably, in step (2), the volume ratio of anhydrous ethanol to water is 2-5:1.

[0025] Preferably, in step (2), the calcination temperature is 300-500° C., and the calcination time is 1-3 h.

[0026] The second aspect of the present invention provides a composite coating-coated graphite composite negative electrode material prepared by the above method.

[0027] The third aspect of the present invention provides the use of the above-mentioned composite coating-coated graphite composite negative electrode material in the preparation of lithium-ion batteries, electric vehicles, portable electronic devices and energy storage systems.

[0028] Beneficial effects of the present invention

[0029] The present invention provides a method for preparing a composite coating-coated graphite negative electrode material, which solves the shortcomings of the graphite negative electrode material in previous designs, such as poor fast charging performance and poor cycle performance. The composite coating-coated graphite negative electrode material prepared by the present invention, the niobium pentoxide coating can reduce the interface impedance, and the titanium dioxide coating can ensure the stability of the structure. The technical advancement is summarized as follows:

[0030] 1. The niobium pentoxide coating in the composite coating-coated graphite negative electrode material reduces the interfacial impedance of the material and improves the rate performance of the material.

[0031] 2. The titanium dioxide coating in the composite coating-coated graphite negative electrode material and niobium pentoxide construct titanium niobium oxide with an octahedral lattice shear structure, which ensures a high degree of structural stability and improves the cycle performance of the material.

[0032] 3. The composite coating material is prepared by a simple sol-gel method and high-temperature calcination method, which has simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 This is a SEM picture of the graphite negative electrode material coated with the composite coating described in the present invention. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0037] Example 1

[0038] A method for preparing the composite coating-coated graphite negative electrode material of the present invention comprises the following steps:

[0039] (1) Dissolve niobium pentoxide in anhydrous ethanol (the mass ratio of niobium pentoxide to anhydrous ethanol is 1 g: 20 mL), add deionized water dropwise (the volume ratio of anhydrous ethanol to deionized water is 3:1), preheat to 40°C and stir for 30 min, add graphite powder (the mass of niobium pentoxide accounts for 10% of the total mass of (graphite + niobium pentoxide)), heat to 80°C and stir until the liquid solvent is evaporated, and obtain solid powder after drying;

[0040] (2) calcining the solid powder obtained in step (1) at 700° C. in a muffle furnace for 3 h to obtain a niobium pentoxide-coated graphite precursor material;

[0041] (3) The precursor material obtained in step (2) is dissolved in an anhydrous ethanol solution (the ratio of the mass of the precursor material to the volume of anhydrous ethanol is 1 g: 20 mL), deionized water (the volume ratio of anhydrous ethanol to deionized water is 3: 1) is added dropwise, and after preheating to 40°C and stirring for 30 min, a tetrabutyl titanate solution (the volume ratio of tetrabutyl titanate to the mass of the precursor material is 1.5 mL: 1 g) is added dropwise, and after heating to 70°C and stirring for 3 h, the solid-liquid mixture in the reaction flask is centrifuged, washed and dried to obtain a solid powder;

[0042] (4) The solid powder obtained in step (3) is calcined in a muffle furnace at 400° C. for 2 h to obtain a composite coating-coated graphite negative electrode material.

[0043] Example 2

[0044] The difference between Example 2 and Example 1 is that in step (3), the mass ratio of the volume of tetrabutyl titanate to the precursor material is 1 mL:1 g, and the other steps, parameters and raw materials remain unchanged.

[0045] Example 3

[0046] The difference between Example 3 and Example 1 is that in step (3), the mass ratio of the volume of tetrabutyl titanate to the precursor material is 0.5 mL:1 g, and the other steps, parameters and raw materials remain unchanged.

[0047] Example 4

[0048] The difference between Example 4 and Example 1 is that in step (3), the mass ratio of the volume of tetrabutyl titanate to the precursor material is 2 mL:1 g, and the other steps, parameters and raw materials remain unchanged.

[0049] Example 5

[0050] The difference between Example 5 and Example 1 is that in step (3), the mass ratio of the volume of tetrabutyl titanate to the precursor material is 2.5 mL: 1 g, and the other steps, parameters and raw materials remain unchanged.

[0051] Comparative Example 1

[0052] Comparative Example 1 is a graphite negative electrode material without any treatment.

[0053] Comparative Example 2

[0054] The difference between Comparative Example 2 and Example 1 is that steps (3) and (4) of Example 1 are omitted, and other steps, parameters and raw materials remain unchanged. A graphite negative electrode material coated with niobium pentoxide is synthesized.

[0055] Comparative Example 3

[0056] The difference between Comparative Example 3 and Example 1 is that steps (1) and (2) of Example 1 are omitted, the precursor material of step (3) is replaced by graphite material, and the other steps, parameters and raw materials remain unchanged. A titanium dioxide-coated graphite negative electrode material is synthesized.

[0057] Table 1 shows the electrical performance data of soft-pack batteries made using the graphite negative electrode materials of Examples 1-5 and Comparative Examples 1-3.

[0058]

[0059] The graphite negative electrode materials of Examples 1-5 and Comparative Examples 1-3 were used with other main materials to make soft-pack batteries for comparison of electrical performance. The formula of the positive electrode material of the soft-pack battery is as follows: lithium iron phosphate active material: 97%; conductive carbon black: 0.8%; CNT (carbon nanotube): 0.5%; PVDF (polyvinylidene fluoride): 1.7%. The formula of the soft-pack battery electrolyte is as follows: (1) The solvent accounts for 80%: a mixed solvent of DMC (dimethyl carbonate), EC (ethylene carbonate), and EMC (ethyl methyl carbonate) is used, and the ratio of the three is 1:1:1; (2) The lithium salt accounts for 19.5%: LiPF6 and LiFSI are used as lithium salt components, and the ratio of the two is 1:1; (3) The additive accounts for 0.5%: FEC (fluoroethylene carbonate) is used as an additive. The results are as follows: 1. Rate performance: Examples 1-5 and Comparative Example 2 all maintain a relatively high capacity retention rate, while Comparative Examples 1 and 3 have low capacity retention rates. It can be seen that the niobium pentoxide coating can improve the rate performance of the material, among which Example 3 has the highest retention rate, reaching 98.11%, and Examples 1, 2, 4, and 5 have lower retention rates than Example 3. It can be seen that the titanium dioxide coating will affect the rate performance of the material to a certain extent. 2. Fast charging performance: Examples 1-5 and Comparative Example 2 all maintain a relatively high constant current ratio, while Comparative Examples 1 and 3 have low constant current ratios. It can be seen that the niobium pentoxide coating can improve the fast charging performance of the material, among which Example 3 has the highest constant current ratio, reaching 96.16%, and Examples 1, 2, 4, and 5 have lower constant current ratios than Example 3. It can be seen that the titanium dioxide coating will affect the fast charging performance of the material to a certain extent. 3. Cycle performance: Examples 1-5, the capacity retention rate of Comparative Example 3 after 500 cycles is higher, while the capacity retention rate of Comparative Examples 1 and 2 after 500 cycles is lower, which shows that the titanium dioxide coating can improve the structural stability of the material; the capacity retention rate of Example 5 is as high as 95.96%, which shows that the thicker the titanium dioxide coating, the better the capacity retention ability, but the rate performance and fast charging performance of Example 5 are lower than those of Examples 1-4. In summary, maintaining appropriate niobium pentoxide and titanium dioxide coating thickness is very important for performance balance, among which the rate performance, fast charging performance, and cycle performance of Example 1 are relatively balanced.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite coating-coated graphite composite negative electrode material, characterized in that: include: (1) preparing a niobium pentoxide-coated graphite precursor material; (2) A titanium dioxide coating is coated on the niobium pentoxide-coated graphite precursor material by a sol-gel method, and the coating is calcined to obtain a titanium dioxide coating.

2. The method for preparing a composite negative electrode material coated with a composite coating according to claim 1, characterized in that: In the niobium pentoxide-coated graphite precursor material, the mass of niobium pentoxide accounts for 5%-15% of the total mass of niobium pentoxide and graphite.

3. The method for preparing a composite negative electrode material coated with a composite coating as claimed in claim 1, characterized in that: The specific preparation method of the titanium dioxide coating comprises: dissolving the niobium pentoxide-coated graphite precursor material in an anhydrous ethanol solution, adding water, stirring and preheating, adding a titanium source solution dropwise, heating to react, and after the reaction is completed, performing solid-liquid separation, washing, and drying to obtain the titanium dioxide coating.

4. The method for preparing a composite negative electrode material coated with a composite coating as claimed in claim 3, characterized in that: The preheating temperature is 30-50°C and the preheating time is 20-40 minutes.

5. The method for preparing a composite negative electrode material coated with a composite coating as claimed in claim 3, characterized in that: The heating temperature is 60-80°C and the reaction time is 2-4h.

6. The method for preparing a composite negative electrode material coated with a composite coating as claimed in claim 3, characterized in that: The volume mass ratio of the titanium source solution to the niobium pentoxide-coated graphite precursor material is 0.5-2.5 mL: 1 g.

7. The method for preparing a composite negative electrode material coated with a composite coating as claimed in claim 1, characterized in that: The mass volume ratio of the niobium pentoxide-coated graphite precursor material to the anhydrous ethanol solution is 1 g: 15-30 mL; Or, the volume ratio of the anhydrous ethanol to water is 2-5:

1.

8. The method for preparing a composite negative electrode material coated with a composite coating as claimed in claim 1, characterized in that: The calcination temperature is 300-500° C., and the calcination time is 1-3 hours.

9. A composite coating-coated graphite composite negative electrode material prepared by the method according to any one of claims 1 to 8.

10. Use of the composite coating-coated graphite composite negative electrode material according to claim 9 in the preparation of lithium-ion batteries, electric vehicles, portable electronic devices and energy storage systems.

Citation Information

Patent Citations

  • Metal-coated oxide nano core-shell structure catalyst and preparation method thereof

    CN102969514A

  • Nano titanium dioxide coated graphite lithium ion battery negative electrode material and preparation method thereof

    CN108574098A

  • Graphene-coated titanium niobium oxide composite electrode material, lithium primary battery and preparation method thereof

    CN109167049A

  • Composite-structure flexible transparent conductive film and preparation method and application thereof

    CN111627597A

  • Niobium pentoxide coated graphite composite negative electrode material and preparation method thereof

    CN114864916A

Cited By

  • Lithium battery modified graphite negative electrode material, preparation method thereof and lithium battery

    CN121687900A